Necropolitics: the religious crisis of mass incarceration in America - Ringer, Christophe Darro (Religion and race, 2021)
"This book argues that the othering and criminalization of Black people in times of crisis is part of the religious meaning of America that fuels the problem of mass incarceration. The author develops a religious interpretation of the significance of these images to America's political economy the produces the very problems we punish as a society"--